Diagnostics of carbon and silicon-based plasmas: from surface chemistry to gas-phase physics - Zhou, Jie, author; Fisher, Ellen R., advisor; Dorhout, Peter, committee member; Grainger, David, committee member; Ladanyi, Branka, committee member; Belfiore, Laurence A., committee member (Colorado State University. Libraries, 2006)
Plasma enhanced chemical vapor deposition (PECVD) has been widely used for deposition of organic polymers and carbon or silicon-based materials. A variety of gas phase, plasma-surface, and surface analysis techniques were used to provide a full understanding of these plasmas. This dissertation first describes the synthesis of a nanostructured composite material formed from plasma-polymerized polypyrrole (PPPy) coated Au fibers. The chemical, structural, and electrochemical characteristics of PPPy films were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and UV-Vis spectroscopy as well as cyclic voltammetry (CV), and scanning electron microscopy (SEM). Higher degree of retained functional group in the polypyrrole backbone was found with increasing duty cycle of pulsed plasma. In addition, as-deposited PPPy films coated on Au nanotubes demonstrate better electrochemical properties than as-deposited PPPy films coated on flat indium tin oxide (ITO) electrodes as a result of the increase in surface area and decrease in film thickness. Langmuir probe and mass spectrometry measurements were used to characterize the gas-phase of low pressure, 13.56 MHz inductively coupled plasmas used for deposition of diamond-like carbon (DLC) thin films. The ionic composition of Ar and CH4/Ar plasma molecular beams was studied using a mass spectrometer with energy analysis capabilities. Low-energy peaks contributed significantly to the total area of the ion energy distributions (IEDs) measured for Ar+ in Ar and CH4/Ar plasmas. In contrast, for all other ions in these systems, the low-energy peaks had a lower contribution to the IEDs as a result of the low probability of energy exchange via ion-neutral collisions. Hydrogenated DLC films were deposited on silicon wafers at different substrate potentials to determine the effect of ion bombardment on film properties. The hydrogen content, surface roughness and deposition rate decreased, whereas the hardness of the films increased when a negative bias voltage was applied. These results demonstrate that ion energy has a significant effect on the composition and morphology of plasma deposited DLC films. The internal and translational energies of gas-phase radicals, SiH and CH, were characterized using laser-induced fluorescence (LIF) for silicon-based (SiH4/Ar and Si2H6/Ar) and carbon-based (CH4/Ar) plasmas. The average rotational temperatures (ϴR) of SiH and CH were found in these plasmas as ~500 K and ~1450 K, respectively, with no obvious dependence on plasma parameters. Modeling of kinetic data yielded average SiH translational temperatures (ϴT) of ~1000 K in the SiHj/Ar plasmas and average CH ϴT of ~2200-2500 K in the CH4/Ar plasmas at 50 mTorr within the studied range. No clear dependence on the argon fraction was observed in both SiH4/Ar and CH4/Ar plasmas. Interestingly, ϴT of SiH in the Si2H6/Ar plasmas decreased from ~1000 K to ~550 K as the Ar fraction in the plasma increases. This indicated that the translational energy of SiH in Si2H6/Ar plasmas has been thermalized with addition of high fraction of Ar gas. In addition, the average CH ϴT did change with applied rf power, ϴT = ~2050-9050 K, which suggests ϴT is associated with the electron temperature in the plasma. The surface reactivity, R, of CH radicals was measured during plasma deposition of amorphous hydrocarbon films using our imaging of radicals interacting with surfaces (IRIS) technique. IRIS combines spatially-resolved LIF with molecular beam and plasma techniques. The measured surface reactivity of CH is near unity and shows no dependence on the applied rf power, argon fraction, substrate temperature, or substrate bias. From these results, CH was clearly involved in film growth despite its low gas-phase density.
Keywords: analytical chemistry